2011
DOI: 10.1002/jcb.23299
|View full text |Cite
|
Sign up to set email alerts
|

H2O2 stimulates Cl−/HCO 3− exchanger activity through oxidation of thiol groups in immortalized SHR renal proximal tubular epithelial cells

Abstract: Cl(-) /HCO (3)(-) exchanger and Na(+) /H(+) exchanger 3 are the main transporters responsible for NaCl reabsorption in kidney proximal tubules (PT). It is well accepted that membrane exchangers can be regulated by reactive oxygen species (ROS). In the kidney, ROS are known to contribute to decreases in Na(+) excretion and consequently increase blood pressure. The present study investigated mechanisms by which H(2) O(2) -induced stimulation of Cl(-) /HCO (3)(-) exchanger activity is enhanced in proximal tubular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In fact, in immortalized SHR PTE cells, H 2 O 2 has been shown to stimulate Cl Ϫ /HCO 3 Ϫ exchanger activity via modification of thiol groups of intracellular and/or transmembrane proteins. The oxidized conformation of the exchanger enhanced the affinity for HCO 3 Ϫ in immortalized SHR PTE cells but not in WKY PTE cells (93). Cysteine residues of proteins are especially susceptible to oxidative stress and, given the important role that disulfides play in protein structure and stability, alterations of reactive cysteine thiol groups may change protein function and activity.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…In fact, in immortalized SHR PTE cells, H 2 O 2 has been shown to stimulate Cl Ϫ /HCO 3 Ϫ exchanger activity via modification of thiol groups of intracellular and/or transmembrane proteins. The oxidized conformation of the exchanger enhanced the affinity for HCO 3 Ϫ in immortalized SHR PTE cells but not in WKY PTE cells (93). Cysteine residues of proteins are especially susceptible to oxidative stress and, given the important role that disulfides play in protein structure and stability, alterations of reactive cysteine thiol groups may change protein function and activity.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…It is widely accepted that oxidative stress contributes to tissue damage, thereby leading to pathological changes during the aging process. In both murine and human studies, researchers reported that aging was associated with increases in reactive oxygen species (ROS) generation and alterations in ROS removal ability [ 6 ]. Furthermore, renal oxidative stress is considered a major factor underlying the initiation of diabetic nephropathy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…ROS can regulate ion transport 1618,23,3564 . Superoxide, produced by NADPH oxidase, enhances NaCl transport in the renal proximal tubule 16,17,39,44,45,59 , thick ascending limb of Henle 41,46,48 , and collecting duct 18,47,48 . The voltage-gated proton channel participates in the increased production of superoxide in the renal outer medulla of Dahl salt-sensitive rats 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Increased ROS production is involved in the pathogenesis of many 1,5,817,22,23,25,2844,48,57,60,6264,68,71,72,86,89,92,104,138,140154,162,163,173,189,197,210,214,218,219,221233,236244,246252,262,263 270273,278280,295,305329331 ,.…”
Section: Introductionmentioning
confidence: 99%